Effectiveness of hand hygiene interventions in reducing illness absence among children in educational settings: a systematic review and meta-analysis. Issue 1 (15th October 2015) - Willmott, Micky; Nicholson, Alexandra; Busse, Heide; MacArthur, Georgina J; Brookes, Sara; Campbell, Rona
Abstract : Objective: To undertake a systematic review and meta-analysis to establish the effectiveness of handwashing in reducing absence and/or the spread of respiratory tract (RT) and/or gastrointestinal (GI) infection among school-aged children and/or staff in educational settings. Design: Randomised-controlled trials (RCTs). Setting: Schools and other settings with a formal educational component in any country. Patients: Children aged 3–11 years, and/or staff working with them. Intervention: Interventions with a hand hygiene component. Main outcome measures: Incidence of RT or GI infections or symptoms related to such infections; absenteeism; laboratory results of RT and/or GI infections. Results: Eighteen cluster RCTs were identified; 13 school-based, 5 in child day care facilities or preschools. Studies were heterogeneous and had significant quality issues including small numbers of clusters and participants and inadequate randomisation. Individual study results suggest interventions may reduce children's absence, RT infection incidence and symptoms, and laboratory confirmed influenza-like illness. Evidence of impact on GI infection or symptoms was equivocal. Conclusions: Studies are generally not well executed or reported. Despite updating existing systematic reviews and identifying new studies, evidence of the effect of hand hygiene interventions on infection incidence in educational settings is mostly equivocal but they may decrease RT infection among children. These results update and add to knowledge about this crucial public health issue in key settings with a vulnerable population. More robust, well reported cluster RCTs which learn from existing studies, are required.